143k views
2 votes
Evaluate the expression 5(x + y) – 3(x – y) if x = 4 and y = -2

User PatL
by
4.8k points

2 Answers

4 votes

Answer:

4

Explanation:

Simply, replace the values we are given for x=4 and y=(-2) into the expression.

5(x + y) – 3(x – y)

5*(4 - 2) - 3*(4 -2)

20 - 10 - 12 + 6 = 4

User Derek Nolan
by
4.7k points
3 votes

Answer:

The value of given expression 5(x + y) -3(x - y) when x = 4 and y = -2 is -8

Solution:

From question, given that

5(x + y)-3(x - y) ---- eqn 1

Given that x = 4 and y = -2

On substituting x = 4 and y = 2 in equation 1, we get

=5(4 - 2) – 3 (4 + 2)

On simplifying above expression

=5(2) – 3(6)

= 10 -18

= -8

Hence value of given expression 5(x + y) -3(x - y) when x = 4 and y = -2 is -8

User Optimus
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.